Morocco - Merrick, Patrick ([Chanhassen, MN] : Child's World, 2001)
Introduces the history, geography, plants, animals, people, and customs of the North African nation of Morocco.
2-5.
Accelerated Reader AR
Includes index.
Keywords: Morocco